Glucose-6-Phosphate Dehydrogenase (G6PD) Deficiency Disease- A Brief Overview - Ashok, Purnima; Thomas, Blessy Maria (Indian Journal of Pharmacy Practice)
G6PD Deficiency is considered as the most frequently seen enzymopathy affecting the erythrocytes. It has high prevalence rates in the regions of tropical Africa, the Middle East, tropical and subtropical Asia. Severe G6PD deficiency is more common in males, inheriting hemizygous G6PD mutations will have defect in all their RBC’s showing abnormal signs and symptoms. Triggering factors for haemolytic anaemia in G6PD deficient patients include medications and other chemical substances, fava beans, infections, etc. These patients show a spectrum of disorders including, acute massive hemolysis, neonatal icterus, renal failure, chronic haemolytic anaemia, etc. There are several tests available for diagnosing G6PD deficiency, genetic testing can be done to confirm the condition. After diagnosing, the patients should do routine checkups for good prognosis. Every G6PD deficient patients do not need treatment always, however identification and discontinuation of the triggering factors is very important to manage hemolysis. Treatment of the condition mainly focuses on the symptoms. All the hospital should utilize computerized supporting tools so that the patients with less common disease conditions like G6PD deficiency will receive rationalized treatment and will help to control this genetic disorder.
Keywords: G6PD Deficiency; Enzymopathy; Haemolytic anaemia; Neonatal icterus; Fava beans